Leaving against medical advice: a mixed method study to explore the prevalence, causes, and challenges in the emirates health services' hospitals - Amna I. Alshamsi; Alaa Abuquta; Alaedin Ibrahim; Amna AlSaadi; Esam Altaee; Najlaa AlAli (Frontiers in Disaster and Emergency Medicine, 2024)
ObjectiveThis study investigated the common reasons for leaving against medical advice (LAMA) at Emirates Health Services (EHS) by comparing electronic medical records (EMR) with healthcare professionals' (HCPs) stated reasons and understanding the challenges faced by HCPs in such cases. We also explored patient-related factors associated with LAMA based on HCP interviews to improve patients' outcome.MethodsThis mixed-method study used EMR data and HCP interviews from four EHS public hospitals with LAMA rates of >2%. EMR variables, including nationality, personal and social reasons, financial reasons, sex, and triage classifications, were dummy-coded and tested using the chi-squared test. Twenty interviews were conducted and analyzed using thematic analysis (TA).ResultsQuantitative data revealed that 5,521 patients left against medical advice in the four hospitals over 6 months. The average age of these patients was 35.1 years (SD = 22.4), and 61.3% were male. Personal and social reasons accounted for 65.7% of the patients who opted for LAMA, and 69.9% were classified as triage 3. There was a significant association between Emiratis and non-Emiratis LAMA and triage category reasons X2 (1) = 138.1, p ≤ 0.001. The odds ratios indicated that Emiratis with triage 3–5 were 2.7 times more likely to leave (95% confidence interval: 2.37–3.38) than non-Emiratis. TA identified two main themes as strategies for managing LAMA: reasons for LAMA and outcomes of LAMA.DiscussionThe results highlight the perspective of HCPs on the reasons for LAMA, providing insights for developing interventions to influence patient decisions and enhance health outcomes. Interventions may include enhancing HCP-patient communication and educating patients on adherence to medical advice. In conclusion, EHS needs strategies to improve LAMA among patients despite of their nationality.